The Influence of Perceived Ease of Use and Perceived Security on Customer Satisfaction Using QRIS (Case Study: Bank Bri Unit Bandar Lampung) - Supiati, Tina; Rinova, Dora (PT Inovasi Pratama Internasional, 2025)
The learning wants to deepen how the perception of ease and security of QRIS affects customer satisfaction at Bank BRI Unit Bandar Lampung. As the national digital payment standard, QRIS has seen significant adoption. However, its success relies not only on ease of use but also on how secure customers feel using it. Data from Bank BRI Unit Bandar Lampung indicates that the number of QRIS users has reached 6,887, highlighting the need to explore the factors that impact customer satisfaction with this digital payment service. Through a literature review, this research identifies two main factors influencing customer satisfaction: ease of use and the security of the payment system. It is hoped that the results can support sales growth digital payment services, especially QRIS. By understanding what influences customer satisfaction, service providers can enhance service quality and increase the user base of QRIS. Then the learning can become material for the next study that explores other aspects of digital payment technology adoption in Indonesia.